The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14185293
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Coefficients for the Renner Model of the Thermodynamic Equation of State of the Poly(butylene succinate) and Wheat Bran Biocomposites

Abstract: This paper presents the assumptions of a thermodynamic equation of state for polymers according to the Renner model. The experiments involved extruding a biocomposite based on poly(butylene succinate) that was filled with ground wheat bran with its size not exceeding 200 μm. The biocomposite was produced in pellet form with three different contents by weight of wheat bran, i.e., 10%, 30% and 50%. All specimens were examined for their thermodynamic p-v-T characteristics. Taking advantage of the SimFit module of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The literature includes numerous papers dealing with the manufacturing and properties of biocomposites on a PBS matrix with the addition of various natural fillers. Examples of such fillers are shredded wood shavings [34]; ground bran of cereals (wheat [35] and rice [36]); nut shells (pistachios [37], peanuts [38], and coconut [39]); and seeds (almonds [40]) but also dried pomace (apple [41] and grape [42]) or even wine lees [43]. The composition of all natural fillers of plant origin is based mainly on cellulose, hemicellulose, and lignin, but they differ in structure as well as in the proportion of their main components and the content of additional substances, such as simple and complex sugars, proteins, fats, and water [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The literature includes numerous papers dealing with the manufacturing and properties of biocomposites on a PBS matrix with the addition of various natural fillers. Examples of such fillers are shredded wood shavings [34]; ground bran of cereals (wheat [35] and rice [36]); nut shells (pistachios [37], peanuts [38], and coconut [39]); and seeds (almonds [40]) but also dried pomace (apple [41] and grape [42]) or even wine lees [43]. The composition of all natural fillers of plant origin is based mainly on cellulose, hemicellulose, and lignin, but they differ in structure as well as in the proportion of their main components and the content of additional substances, such as simple and complex sugars, proteins, fats, and water [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…This article is a continuation of a comprehensive study of the properties of polymer biocomposites containing wheat bran. Studies of the physical and processing properties of the compositions carried out so far by the authors of this article have shown that the bran content has a significant effect on these properties [14][15][16][17]43,44]. The purpose of the presented study was to determine the effect of using a filler in the form of wheat bran on the flammability of the obtained polymer biocomposition.…”
Section: Introductionmentioning
confidence: 96%
“…Their most common sources are plant fragments that constitute process waste from agriculture, food, wood or textile industries, which act as fillers for polymer compositions [2,3,[5][6][7][8]. These include rice bran and hulls [9][10][11][12], wheat bran [13][14][15][16][17], shells from various nut species [18][19][20][21][22][23][24], dust from various tree species [8,25,26], residues from palm oil production [27] and sugarcane (bagasse) processing [28], wheat straw [29], sunflower and corn stalks [30], and barley hulls [31]. Such fillers, whose main components are cellulose, hemicellulose and lignin, are called lignocellulosic fillers [13,25].…”
Section: Introductionmentioning
confidence: 99%